Dangerous Writing: understanding the political economy of composition - Tony Scott (Utah State University Press, 2009)
Building on recent work in rhetoric and composition that takes an historical materialist approach, Dangerous Writing outlines a political economic theory of composition. The book connects pedagogical practices in writing classes to their broader political economic contexts, and argues that the analytical power of studentsâ€™ writing is prevented from reaching its potential by pressures within the academy and without, that tend to wed higher education with the aims and logics of â€œfast-capitalism.â€